Pendampingan Anak Sebagai Korban Kekerasan Seksual Oleh Dinas Pemberdayaan Perempuan Perlindungn Anak Dan Keluarga Berencana (DPPPAKB) Kota Pangkalpinang - Ragina Aprilia; Toni; Rio Armanda Agustian (CV. Multi Kreasi Media, 2025)
Sexual violence against children is a serious and concerning social issue that has severe negative impacts, both physically and psychologically, on the victims. Therefore, recovery efforts through assistance and support are essential for children who have experienced sexual violence. One of the institutions responsible for providing such support is the Office for Women's Empowerment, Child Protection, and Family Planning (DPPPAKB). This study aims to examine the role and forms of assistance provided by DPPPAKB in Pangkalpinang City to child victims of sexual violence, as well as to identify the challenges faced in its implementation. The research employs an empirical method with a qualitative approach, using interviews and documentation as data collection techniques. The findings indicate that DPPPAKB Pangkalpinang plays a crucial role in assisting victims by providing them with a sense of security and emotional support. The forms of assistance offered include legal support, mediation, and psychological counseling. However, several obstacles were identified in the implementation process, including limited funding, a shortage of support personnel, victims' reluctance to share their experiences, a lack of public awareness campaigns on preventing sexual violence, and insufficient parental and community involvement in child protection efforts.